Occupation and small bowel adenocarcinoma: a European case-control study. Issue 11 (1st November 2000) - Kaerlev, Linda; Teglbjaerg, Peter Stubbe; Sabroe, Svend; Kolstad, Henrik A; Ahrens, Wolfgang; Eriksson, Mikael; González, Agustin Llopis; Guénel, Pascal; Hardell, Lennart; Launoy, Guy; Merler, Enzo; Merletti, Franco; et al.
Abstract : OBJECTIVES: Because of the rarity of small bowel adenocarcinoma (SBA), little is known about the aetiology of this disease. This study aimed to identify occupational clustering of cases SBA as a systematic approach to new hypotheses on the aetiology of this disease. METHODS: A European multicentre case-control study was conducted in 1995–7, inclusive. Incident cases aged 35–69 years with SBA (n=168) were recruited before acceptance by a pathologist. Altogether 107 cases and 3915 controls were accepted, of which 79 cases, 579 colon cancer controls, and 2070 population controls were interviewed. RESULTS: The strongest industrial risk factors for SBA taking account of 10 years' exposure lag were dry cleaning, manufacture of workwear, mixed farming (women), and manufacture of motor vehicles (men). A significantly increased risk of SBA (odds ratio (OR) and 95% confidence interval (95% CI)) was found among men employed as building caretakers, OR 6.7 (1.7 to 26.0) and women employed as housekeepers, OR 2.2 (1.1 to 4.9); general farm labourers, OR 4.7 (1.8 to 12.2); dockers, OR 2.9 (1.0 to 8.2); dry cleaners or launderers, OR 4.1 (1.2 to 13.6); and textile workers (sewers or embroiders), OR 2.6 (1.0 to 6.8). For the last four groups, together with welders OR 2.7 (1.1 to 6.6) (men) an exposure-response pattern was found when calculating the ORs for jobs held 1–5 years and >5 years, with never having held the job as reference. The ORs (95% CIs) for 1–5 years and >5 years were 4.3 (0.4 to 44.0) and 3.5 (0.9 to 13.7), 3.0 (0.3 to 26.2) and 4.3 (0.9 to 21.2), 4.6 (0.4 to 48.1) and 11.0 (2.0 to 60.4), 1.3 (0.2 to 11.0) and 5.8 (2.0 to 17.2), and 2.8 (0.3 to 23.8) and 4.6 (1.3 to 16.6), respectively, for each of these occupations. Among welders, people performing semiautomatic arc welding (MIG/MAG) were identified as a high risk group (OR 5.0 (1.3 to 19.6)). CONCLUSIONS: This explorative study suggests an increased occurrence of SBA in certain occupations, which needs further evaluation.